Religion, violence, and local power-sharing in Nigeria - Vinson, Laura Thaut
"Why does religion become a fault line of communal violence in some pluralistic countries and not others? Under what conditions will religious identity - as opposed to other salient ethnic cleavages - become the spark that ignites communal violence? Contemporary world politics since 9/11 is increasingly marked by intra-state communal clashes in which religious identity is the main fault line. Yet, violence erupts only in some religiously pluralistic countries, and only in some parts of those countries. This study argues that prominent theories in the study of civil conflict cannot adequately account for the variation in subnational identity-based violence. Examining this variation in the context of Nigeria's pluralistic north-central region, this book finds support for a new theory of power-sharing. It finds that communities are less likely to fall prey to a divisive narrative of religious difference where local leaders informally agreed to abide by an inclusive, local government power-sharing arrangement"--
"Of course, Nigeria is not the only country where ethnic or inter-religious violence is now a major security challenge. Indeed, reports of religious communal violence or riots in many countries frequent the headlines, coinciding with the global resurgence of religion and its politicization and radicalization. Countries such as India, Indonesia, Nigeria, Myanmar, Egypt, Malaysia, Ethiopia, the Central African Republic - to name a few - have been or continue to be flashpoints of inter-religious violence. Other countries such as Ghana, Tanzania, and Kenya, face increasing tensions among their religious groups, and religious cleavages are present in major conflicts in the Middle East, such as in Iraq and Syria. In many of these cases, a vitriolic religio-political discourse infuses the public space, blurring the lines between the politics of church and state. The rapid transformation of the religious composition of many countries in the global South since the 1970s, the increase in intra-state conflict, and watershed events such as the Iranian Revolution in 1979 and the U.S. 9/11 attacks have raised the specter of a world increasingly characterized by religiously-motivated violence"--
Machine generated contents note: Acknowledgements; Preface; 1. Deterring religious violence; Part I. The Importance of Local Government and the Politics of Religious Change: 2. Pattern and politics of religions change in Nigeria; 3. Tenuous unity: federalism, local governments, and politics in Nigeria; Part II. Making the Case for Power-Sharing: The Empirical Evidence: 4. Theory of local government power-sharing; 5. Power-sharing data and findings; 6. Case studies and the power-sharing mechanism; 7. Case studies and the origins of power-sharing; 8. Considering competing hypotheses; Part III. Conclusions: 9. Conclusion; Appendices; References; Index.
Keywords: Local government; Religion and state; Coalition governments; Political violence; Ethnic conflict; Nigeria; POLITICAL SCIENCE / Government / General